Data Envelopment Analysis Models to Measure the Relative and Scale Efficiency of Educational Institutions (Tikrit University as A Model) - Omar AL-Sultany; Oday Jarjies (المجلة العراقية للعلوم الاحصائية)
The research dealt with measuring the relative efficiency and scale efficiency of the colleges of Tikrit University for the academic year (2019-2020) using the data envelope analysis (DEA) method, which is one of the linear programming methods to measure the productive efficiency of institutions and economic units. The constant returns to scale (CCR) model and the variable returns to scale (BCC) model were used according to the input-oriented measures and output-oriented measures indicators. In order to achieve the objectives of the study, the 21 colleges of the University of Tikrit were selected, and three inputs were identified: the number of registered students, the number of teaching staff, the number of employees, and two outcomes (the number of graduates and the number of published research, seminars, and conferences). The research reached several results, the most important of which is that (9) colleges achieved relative efficiency in the CCR model and (11) colleges in the BCC model with both internal and external orientations. The research also addressed the necessary procedures and reforms for incompetent colleges for the purpose of reaching competency, and also identified the reference colleges for each incompetent college to imitate and emulate in order to reach full competency.